Revisi Undang-Undang Nomor 35 Tahun 2009 Tentang Narkotika: Pengaturan Zat Psikoaktif Baru - Diah Pratiwi, Andriani Mutia; Christiana, Christiana; Renel, Rosita Dewi Eka (UI Scholars Hub, 2022)
Massive technological and information developments have had an impact on the emergence of new types of drugs or new psychoactive substances (NPS). NPS is a new chemical synthesis designed to imitate the psychoactive effects of legally controlled drugs. Developing and establishing flexible and appropriate legislation is necessary to monitor the circulation and abuse of NPS. This article uses a qualitative method with a normative legal approach based on secondary evidence (literature review). To date, the NPS regulations have been included in the schedule to Narcotics Act No. 35, 2009, which is regulated by the Minister of Health. Assessment of a type of NPS takes six months to two years, so the number of identified NPS is not as quick as published regulations. The EU through EMCDDA uses an early warning system in reporting new substances, an assessment mechanism and risk control in NPS law enforcement. Meanwhile, China uses the NPS conversion system with a certain amount of narcotics to convict perpetrators. To counter the threat of abuse and the illicit flow of NPS in Indonesia, a comprehensive policy is needed. Policies to combat NPS abuse and illicit traffic should not only be measured based on indicators of the number of people arrested or imprisoned for NPS violations and the number confiscated, but also based on health, development and human rights. Keywords: Narcotics, New Psychoactive Substances, Law Enforcement